Reflexiones en torno a la enseñanza del derecho en un contexto latinoamericano - Mora Amezcua, Haydee Maricela (2022)
This paper reflects on the legal discipline and the challenges it has in university education. Legal science, throughout its history, has sought to remain intact in its pedagogical process, without taking into account current educational needs. In this work, this traditional education is questioned and alternatives are proposed to carry out a legal education hand in hand with the needs of today's society.